INDONESIAN PRE-SERVICE ENGLISH TEACHERS’ ATTITUDES TOWARDS THE USE OF WORLD ENGLISHES IN INTERNATIONAL ENGLISH PROFICIENCY TESTS: A SMALL-SCALE SURVEY (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
While a considerable number of English language users come from expanding-circle countries, international English proficiency tests like TOEFL and IELTS tend to model inner-circle varieties like British, North American, and Australian, implying that inner-circle varieties are more preferable. This quantitative study investigated the attitudes of Indonesian student teachers of English towards the use of World Englishes (WE) in international English proficiency tests like TOEFL and IELTS. 86 student teachers from the same cohort at a private university in Indonesia were involved. The data were collected using an 18-item questionnaire adopted from Monfared (2020) and then analyzed statistically using SPSS. The results of this study indicated that the participants generally acknowledged the idea of the use of World Englishes in international English proficiency tests, but they tended to disapprove deviations from standard English grammar and vocabulary. The implications of this study are also discussed.